Gender and regional variation in fruit and vegetable consumption and determinants among 11- to 13- year old Portuguese children - Wind, M. (2010)
Objective Results from the European Pro Children study showed that intake of fruit and vegetables was highest among Portuguese children, but still lower than the daily recommended intake levels. The objective of this study was to identify gender and regional differences in intake and related personal and environmental determinants among 11-to 13-year old Portuguese children. Design/setting/subjects As part of the Pro Children study a cross-sectional survey was carried out in October-December 2003 among 2134 Portuguese children and 1314 mothers. Data was collected by means of self-administered questionnaires. Intake was assessed by a 24-hour recall and food frequency questions. Potential determinants were demographic, personal, perceived social-environmental and perceived physical-environmental factors and mother's frequency of intake. Results Children's intake of fruit and vegetables was low for both genders and in all regions. Boys reported less frequent intake than girls in all regions except for fruit in Lisboa. Children from Lisboa and Algarve reported lowest mean and least frequent intake of fruit and vegetables. Knowledge of daily recommended intake levels, taste preferences, perceived parental modelling behaviour, and mother's intake were strongest associated with children's daily intake of fruit and vegetables. These determinants were associated fairly consistently across genders and regions. Conclusions This study did not reveal large gender and regional differences in determinants related to intake of fruit and vegetables. Interventions should in particular address children's knowledge and taste preferences and parental intake.